Candidemia in Pediatric Patients: Changing Pattern of Isolated Candida Species and Risk Factors in Eastern India. - Chaudhury, Nabamita; Biswas , Tanusri; Mondal , Raston; Chattopadhyay , Saswati; Mandal , Deblakshmi; Mukherjee , Nivedita; Arghya Nath; Soumyendranath Das (International Journal of Endorsing Health Science Research, 2023)
Background: Candidemia is a life-threatening bloodstream infection caused by Candida species and is a major concern in pediatric patients, particularly in developing countries like India. Therefore, the goals of the current study are to isolate and identify several Candida species from blood samples, link various risk factors with candidemia, and ascertain the antifungal sensitivity pattern of each species. Methodology: This study is an observational, cross-sectional study conducted to determine the prevalence, distribution, and antifungal susceptibility of Candida species among pediatric patients with candidemia. The current study collected blood samples in BACT/ALERT 3D Pediatric bottles for fungal blood culture. After positive growth was obtained from Blood agar and Sabouraud's dextrose agar (SDA), a range of biochemical reactions, including Gram staining, Germ tube test, CHROM agar Candida Medium, and Sugar fermentation, were carried out. The Kirby-Bauer disc diffusion method was used for conducting the antifungal susceptibility test. Results: Among the total of 156 different species of Candida, the maximum isolates were Candida albicans (CA) (42.9%), followed by Candida tropicalis (23.1%) and Candida parapsilosis (14.7%). The Pediatric Intensive Care Unit (PICU) had the most Candida isolates, and catheterization was a leading risk factor. Susceptibility to Amphotericin B, Caspofungin, and Voriconazole was 84.6%, 81.4%, and 76.9%, respectively. Our study observed that the azole group of antifungals revealed pretty high resistance to Non-Candida albicans (NCA). Conclusion: The prevalence of candidemia was higher in the pediatric ICU and neonatal ICU, and the incidence rate was highest among neonates and infants. The study concludes that NCA species are gradually replacing C. albicans as an important pathogen, and clinicians need to be aware of the antifungal resistance patterns of the different Candida species.